Voting at the political fault line : California's experiment with the blanket primary - Cain, Bruce E.; Gerber, Elisabeth R., 1964-; University of California, Berkeley. Institute of Governmental Studies (Berkeley : University of California Press, 2002)
California's adoption of the blanket primary in 1996 presented a unique natural experiment on the impact that election rules have on politics. Billed as a measure that would increase voter participation and end ideological polarization, Proposition 198 placed California voters once again on the frontier of political reform.
California's blanket primary experiment / Bruce E. Cain and Elisabeth R. Gerber -- Crossover voting before the blanket: primaries versus parties in California history / Brian J. Gaines and Wendy K. Tam Cho -- Political reform via the initiative process: what voters think about when they change the rules / Shaun Bowler and Todd Donovan -- Context and setting: the mood of the California electorate / Mark Baldassare -- The causes and consequences of crossover voting in the 1998 California elections / John Sides, Jonathan Cohen, and Jack Citrin -- Should I stay or should I go? Sincere and strategic crossover voting in California assembly races / R. Michael Alvarez and Jonathan Nagler -- Peeking under the blanket: a direct look at crossover voting in the 1998 primary / Anthony M. Salvanto and Martin P. Wattenberg -- Crossing over when it counts: how the motives of voters in blanket primaries are revealed by their actions in general elections / Thad Kousser -- Candidates, donors, and voters in California's blanket primary elections / Wendy K. Tam Cho and Brian J. Gaines -- Strategic voting and candidate policy positions / Elisabeth R. Gerber -- Openness begets opportunity: minor parties and California's blanket primary / Christian Collet -- Thinner ranks: women as candidates and California's blanket primary / Miki Caul and Katherine Tate -- Targets of opportunity: California's blanket primary and the political representation of Latinos / Gary M. Segura and Nathan D. Woods -- Candidate strategy, voter response, and party cohesion / John R. Petrocik -- The blanket primary in the courts: the precedent and implications of California Democratic Party v. Jones / Nathaniel Persily -- Strategies and rules: lessons from the 2000 presidential primary / Bruce E. Cain and Megan Mullin.
"Published in association with the Institute of Governmental Studies."
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Primaries -- California; Élections primaires -- Californie; POLITICAL SCIENCE -- Political Process -- Political Parties; HISTORY -- United States -- State & Local -- West (AK, CA, CO, HI, ID, MT, NV, UT, WY); Primaries; California